Synthesis of Novel Spiro Thiazolotriazole Derivatives via 1,3-Dipolar Cycloaddition of Azomethine Ylide - Xiaofang, Li; Bin, Liu; Haochong, Liu; Xianyong, Yu; Pinggui, Yi (Journal of heterocyclic chemistry, 2012)
The 1,3‐dipolar cycloaddition of azomethine ylide generated in situ from isatin and sarcosine to 5‐arylmethylidene thiazolo[3,2‐b][1,2,4]triazol‐6(5H)‐ones afforded novel 1′‐methyl‐4′‐aryldispiro[indole‐3,2′‐pyrrolidine‐3′,5″‐[1,3]thiazolo[3,2‐b][1,2,4]triazole]‐2,6″ (1H)‐diones in moderate yields. The structures of all the products were characterized thoroughly by NMR, infrared spectroscopy (IR), mass spectroscopy (MS) elemental analysis together with X‐ray crystallographic analysis.